Reduced intensity conditioning regimens including alkylating chemotherapy do not alter survival outcomes after allogeneic hematopoietic cell transplantation in chronic lymphocytic leukemia compared to low-intensity non-myeloablative conditioning - Andersen, Niels Smedegaard; Dreger, Peter; Schönland, Stefan (Journal of cancer research and clinical oncology, 2019)
Purpose: The optimal dose intensity for conditioning prior to allogeneic hematopoietic stem cell transplantation (alloHSCT) for chronic lymphocytic leukemia (CLL) is unknown. Methods: We retrospectively compared outcomes of patients who received a first alloHCST after non-myeloablative (NMA) and reduced intensity conditioning (RIC). Data of 432 patients with a median age of 55 years were included, of which 86 patients underwent NMA and 346 RIC. Results: The median follow-up after alloHSCT was 4.3 years. Compared to the RIC group, more NMA patients had purine-analog-sensitive disease, were in complete remission and received matched related donor transplantation. After RIC, the probabilities for 5-year OS, EFS, CIR, and NRM were 46%, 38%, 28%, and 35% and after NMA the respective probabilities were 52%, 43%, 25%, and 32%. In multivariate analysis, remission status prior to conditioning but not RIC versus NMA conditioning had a significant impact on CIR, EFS, and OS.ConclusionPresumed higher anti-leukemic activity of RIC versus NMA conditioning did not translate into better outcomes after alloHSCT, but better remission status prior to conditioning did. Effective pathway inhibitor-based salvage therapies combined with NMA conditioning might thus represent the most attractive contemporary approach for alloHSCT for patients with CLL.